Strategi Pengembangan Potensi Agrowisata Di Kawasan Kebun Kurma Desa Cijeungjing, Kabupaten Ciamis - Alim, Azmi Kautsar; Haris, Iir Abdul; Nugraha, Fikri Sandi (JURNAL DESTINASI PARIWISATA, 2023)
Cijeungjing Village has great potential to be developed into a tourism village, which is through the development of agro-tourism in the Dates Farm. The uniqueness of the date palm is very rarely found in Indonesia. The Dates Garden in Cijeungjing Village also has another added value because it is located on the tourism crossing between Bandung City and Pangandaran Regency. However, the geographical advantage and potential of the Dates Garden owned by Cijeungjing Village has not been exposed because it has not been managed as a tourist destination. This study aims to developed the Dates Farm as a tourist attraction in Cijeungjing Village. This study uses a qualitative descriptive analysis method and a SWOT analysis to get a comprehensive picture of the potential and development strategies in the Cijeungjing Dates Farm. The results showed that various potential attractions were owned, such as date palm farm, food farm, animal farm, and the Cileueur River. This area is also easy to reach and has several facilities such as study centers and residences. Therefore, there is a need for strategies to develop the Cijeungjing Date Palm Farm. First is by packaging agronomic activities into agro tour packages. Second, utilizing digital media to increase promotion. Last, apply the principles of sustainable tourism by collaborating with the community and building a circular economy. Hopely that the development of agrotourism in the Cijeungjing Date Palm Farm can encourage Cijeungjing Village to become a tourist village. Keywords: Dates Palm; Tourism Destination; Agrotourism; SWOT Analysis